The Potentials of Bongkar Ratoon and Good Agricultural Practices (GAP) for Sugar Productivity and Self-Sufficiency in Indonesia - Ghani, Mohammad Abdul; Wibowo, Dradjad Hari; Mahmudi; Harahap, Iman Yani; Kuswurjanto, Risvan; Widyasari, Titik; Permadhi, Danang; Indriawan, Pugar; Kusumawati, Anna; Nugroho, Reismaya Wanamertan (The Indonesian Forestry Certification Cooperation, 2025)
To attain national sugar self-sufficiency by 2030, the Indonesian government has issued Presidential Regulation No. 40/2023 stipulating acceleration of sugar self-sufficiency and supplies of bioethanol as a biofuel. This paper discusses strategies and practical programs to increase productivity as mandated by the Presidential Regulation, using literature reviews and a gap analysis on secondary data obtained from four demo-plots involving plantation companies and farmers. With a land size ranging from 4.4 to 8.4 hectares, each demo-plot applied bongkar ratoon (replacing ratoon with plant cane) and other key components of sugarcane's Good Agricultural Practices (GAP). They include plant variety and maturity recomposition, correct and timely doses of fertilization and water management. The results show that bongkar ratoon and GAP raise productivity from around 5 tons of sugar/hectare to 8.73 - 20.14 tons of sugar/hectare. While the results show promising potentials, expanding the demo-plots into large scale plantations is not straightforward, requiring comprehensive strategies, programs and action plans, some of which are outlined in this paper for both Holding Perkebunan Nusantara's smallholder- and own-plantations.